Location management for next-generation personal communications networks. - Wong, V.W.-S (IEEE Network : the magazine of global information exchange)
This article presents a survey on location management algorithms for next-generation personal communications networks. We first describe different static and dynamic location update algorithms. Then we discuss various selective paging strategies. We also present various modeling techniques that have been used for the performance analysis of location update and terminal paging. We conclude by stating a number of open problems that need to be addressed for the deployment of next-generation PCNs